Post-peak dynamics of a national Omicron SARS-CoV-2 epidemic during January 2022 - Elliott,P; Eales,O; Bodinier,B; Tang,D; Wang,H; Jonnerby,J; Haw,D; Elliott,J; Whitaker,M; Walters,C; Atchison,C; Diggle,P; et al. (2022)
Background: Rapid transmission of the SARS-CoV-2 Omicron variant has led to the highestever recorded case incidence levels in many countries around the world.Methods: The REal-time Assessment of Community Transmission-1 (REACT-1) study hasbeen characterising the transmission of the SARS-CoV-2 virus using RT-PCR test results fromself-administered throat and nose swabs from randomly-selected participants in England atages 5 years and over, approximately monthly since May 2020. Round 17 data were collectedbetween 5 and 20 January 2022 and provide data on the temporal, socio-demographic andgeographical spread of the virus, viral loads and viral genome sequence data for positiveswabs.Results: From 102,174 valid tests in round 17, weighted prevalence of swab positivity was4.41% (95% credible interval [CrI], 4.25% to 4.56%), which is over three-fold higher than inDecember 2021 in England. Of 3,028 sequenced positive swabs, 2,393 lineages weredetermined and 2,374 (99.2%) were Omicron including 19 (0.80% of all Omicron lineages)cases of BA.2 sub-lineage and one BA.3 (0.04% of all Omicron) detected on 17 January 2022,and only 19 (0.79%) were Delta. The growth of the BA.2 Omicron sub-lineage against BA.1and its sub-lineage BA.1.1 indicated a daily growth rate advantage of 0.14 (95% CrI, 0.03,0.28) for BA.2, which corresponds to an additive R advantage of 0.46 (95% CrI, 0.10, 0.92).Within round 17, prevalence was decreasing overall (R=0.95, 95% CrI, 0.93, 0.97) butincreasing in children aged 5 to 17 years (R=1.13, 95% CrI, 1.09, 1.18). Those 75 years andolder had a swab-positivity prevalence of 2.46% (95% CI, 2.16%, 2.80%) reflecting a highlevel of infection among a highly vulnerable group. Among the 3,613 swab-positiveindividuals reporting whether or not they had had previous infection, 2,334 (64.6%)reported previous confirmed COVID-19. Of these, 64.4% reported a positive test from 1 to30 days before their swab date. Risks of infection were increased among essential/keyworkers